The Effectiveness of Ethanol Extract Botto’-Botto’ Leaves (Chromolaena Odorata L.) in Transdermal Patch Formulation as Medication in Wound Healing - Masri, Anshari; Nurfadilah; Zulkifli; Duppa, Muhammad Taufiq; Sibadu, Muhammad Subhan A (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2022)
Botto’-botto’ plant (Chromolaena odorata L.) is a native Indonesian plant that belongs to the Asteraceae family and is known to have a high flavonoid content and antioxidant activity that can slow down the oxidation process to prevent infection while accelerating wound healing. botto’-botto’ is designed as a patch to make it easier to use and provide the most effective treatment. The purpose of this study was to make a patch preparation and to investigate its effects on wound healing. The patch was formulated and then tested for physical properties (organoleptic, superficial pH, moisture loss, thickness, weight uniformity, and folding endurance test) and their activity against wounds experimentally using rabbits as an animal test with 4 (four) treatment groups, namely the control group, botto’-botto’ patch 10%, 20%, and 30%. Wounds were made with an area of 2 cm and 0.1 cm deep. The wound was plastered with a patch and observed for 18 days. Data were analyzed statistically using ANOVA. The results showed that the patch formulation of leaves extract botto’-botto’ affects for wound healing in rabbits significantly, with p<0.05. Furthermore, the patch formulation of ethanol extract botto’-botto’ with a concentration of 30% had the best and fastest healing effect among all formulas. KEYWORDS: Botto’-botto’, wound healing, transdermal patch